New drugs for the treatment of hyperlipidemia in statin-intolerant patients - review - Wojtek Płonka; Marcin Pelc; Gracjan Sitarek; Marta Żerek; Monika Bułatowicz; Joanna Liber; Krzysztof Banach; Damian Chruścicki; Aleksandra Pławiak (Journal of Education, Health and Sport, 2024)
Introduction